A high-fidelity simulation of the primary breakup within suspension high velocity oxy fuel thermal spray using a coupled volume of fluid and discrete phase model. (December 2020) - Chadha, S.; Jefferson-Loveday, R.; Hussain, T.
Highlights: Coupled VOF and DPM model employed to model the primary breakup for combustion applications. Investigated the effect of a co-annular liquid injector for suspension. Investigated the effect of the injection Weber number. Comparison of Sauter mean diameter to experimental measurements within literature. Abstract: In the suspension high velocity oxy fuel (SHVOF) thermal spray, a suspension is injected into the combustion chamber where the jet undergoes primary and secondary breakup. Current knowledge of the primary breakup within the combustion chamber is very limited as experimental investigations are impeded due to direct observational inaccessibility. Numerical methods are also limited due to the computational costs associated with resolving the entire range of multiphase structures within SHVOF thermal spray. This paper employs a coupled volume of fluid and discrete phase model, combined with a combustion model, to simulate primary breakup at a fraction of the cost of a fully resolved simulation. A high-fidelity model is employed within this study to model the combustion chamber; the model shows a backflow region that will contribute to clogging within the nozzle. This study modifies the injector type for SHVOF thermal spray by introducing a co-flow around the liquid injection to reduce clogging within the combustion chamber. This study shows that introducing a co-flow of gas at a velocity of 200 m/s around the liquid injection reduces the backflow region by 40% within the combustion chamber. The addition of a gas co-flow results in a smaller region of backflow. Small suspension droplets with insufficient momentum are unable to overcome the backflow and will likely deposit themselves onto the wall of the combustion chamber. The deposition of the particles on the walls causes clogging of nozzles often seen in SHVOF thermal spray. The addition of a gas co-flow results in an increase in the velocity of droplets formed during primary breakup. The greater droplet velocity allows for small droplets to overcome the small backflow region near the liquid injection. The Sauter mean diameters predicted from the numerical model are compared to experimental measurements available within the literature and shows good agreement.